HUBUNGAN POLA ASUH ORANG TUA DENGAN PERILAKU SEKSUAL REMAJA DI SMPN 2 LUBUK ALUNG - ELIZA ELIZA (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2022)
Sexual behavior in adolescents can have a detrimental impact on the development and health of adolescents. Based on a survey (SKRRI) it was found that 10% of adolescents aged 15-19 years had given birth to their first child. The purpose of this study was to determine the relationship between parenting style and adolescent sexual behavior at SMPN 2 Lubuk Alung in 2022. The research design used a correlational research design in the form of cross sectional. The population is 140 students with a sampling technique that is simple random sampling, with a total sample of 40 students. The research was carried out from May-August 2022 using a randomized questionnaire distribution technique. Data were analyzed univariately using the frequency distribution and bivariate analysis using the Chi Square test with a confidence level of 95% ? < 0.005. The results showed that there were 15 respondents (37.5%) democratic parenting styles, 21 respondents (52.5%) authoritarian parenting styles. As many as 27 respondents (67.5%) were at risk of sexual behavior and 13 respondents (32.5%) were not at risk. There is a relationship between parenting style and adolescent sexual behavior (P = 0.003). It is hoped that parents will maintain good relations with children so that children feel safe and comfortable at home and it is hoped that parents will not consider it a taboo in talking about sexual education for children. ABSTRAKPerilaku seksual pada remaja dapat menimbulkan dampak yang merugikan pada perkembangan dan kesehatan remaja. Berdasarkan survei (SKRRI) didapatkan 10% remaja berumur 15-19 tahun pernah melahirkan anak pertama. Tujuan penelitian ini untuk mengetahui hubungan pola asuh orang tua dengan perilaku seksual remaja di SMPN 2 Lubuk Alung tahun 2022. Desain penelitian ini menggunakan rancangan penelitian korelasional berupa cross sectional. Populasi berjumlah 140 siswa dengan teknik pengambilan sampel yaitu simple random sampling, dengan jumlah sampel 40 siswa. Penelitian dilaksanakan dari Mei-Agustus 2022 dengan teknik penyebaran angket dengan secara acak. Data dianalisi secara univariat mengunakan distribusi frekuensi dan analisis bivariat menggunakan uji Chi Square dengan tingkat kepercayaan 95 % ?< 0,005. Hasil menunjukkan bahwa terdapat pola asuh demokratis sebanyak 15 responden (37,5%), pola asuh otoriter sebanyak 21 responden (52,5%). Sebanyak 27 responden (67,5%) remaja berisiko berperilaku seksual dan tidak berisiko sebanyak 13 responden (32,5%). Terdapat hubungan pola asuh orang tua dengan perilaku seksual remaja (P= 0,003). Diharapkan kepada orang tua untuk tetap menjaga hubungan baik dengan anak agar anak merasa aman dan nyaman berada di rumah dan di harapkan orang tua tidak menganggap tabu dalam membicarakan tentang pendidikan seksual terhadap anak.